The 22 April 1991 Limón, Costa Rica tsunami field survey - Nishenko, Stuart (2021)
A small tsunami (tsunami magnitude, m ~ 1) was observed following the 22 April 1991 Mw 7.7 Limón, Costa Rica earthquake along the Caribbean coast of Costa Rica and Panama. This report summarizes eyewitness observations from 26 sites along 150 km of affected coast from Rio Matina, Costa Rica to Bocas del Toro, Northwestern Panama, as well as tide gauge recordings from Panama, Puerto Rico and the Virgin Islands. No emergency warnings were issued before the tsunami occurred. While little or no tsunami-related property damage was reported, two or more drownings were attributed to the tsunami. The maximum runup/wave height was reported to be 2 to 3 m, and inundation and coastal flooding extended up to 100 m inland in some locations. Both coseismic coastal uplift and the presence of fringing offshore reefs appear to have provided protection against major runup effects in some coastal areas. Elsewhere, runup effects were amplified at river mouths due to differential compaction of unconsolidated sediments. Widespread tsunami sand deposition near the Costa Rica-Panama border in 1991 is similar to deposition associated with the 7 May 1822 earthquake and tsunami.